The Effect of GTAW Variants on Tensile and Microstructural Properties of AZ31B Magnesium Alloy Joints. (3rd October 2022) - Subravel, V.; Padmanaban, G.; Rajamurugan, T. V.; Seeman, M.; Chandrasekaran, V.; Rajaganapathy, C.; Lenin, Haiter A.
Abstract : In this investigation, an attempt is made to study the tensile and microstructural impact of different gas tungsten arc (GTA) welding processes of pulsed current, constant current, and magnetic arc oscillation welded AZ31B magnesium metal joints. These techniques were chosen because they have the potential to produce welds with high tensile strength and excellent microstructural integrity. Five joints were produced using each approach, each one employing a unique combination of parameters. According to the findings of this experiment, the joints that were manufactured utilising a welding process called magnetic arc oscillation yielded superior tensile qualities when compared to the properties of other joints. The improved tensile characteristics of these joints can be ascribed in a large part to the creation of smaller grains and surface hardness in the transition region, as well as uniformly dispersed precipitates.